2021
DOI: 10.1007/s40430-021-03314-9
|View full text |Cite
|
Sign up to set email alerts
|

Elastohydrodynamic behavior analysis on water-lubricated journal bearing: a study of acoustic and tribological performance based on CFD-FSI approach

Abstract: Most of the studies with respect to the use of water-lubricated journal bearing are mainly concerned with tribological performance, whereas few studies explore the noise characteristics of such bearing. In this study, the tribological and acoustic behavior of water-lubricated journal bearing is studied using a rigorous program containing combined CFD and two-way FSI procedures for simulating elastohydrodynamic simulation for a range of different bearing materials. To model cavitation in the bearing, the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 31 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that the Reynolds decomposition, which includes the breakdown of an instantaneous quantity into its time-averaged and fluctuating components, is the primary technique for deriving the RANS equations from the instantaneous Navier-Stokes equations. The separation of a variable (such as velocity u) into its mean (time-averaged) component (ū) and its fluctuating component (u′) is referred to as Reynolds decomposition [12]. The expressions for the continuity equation and the RANS equation are as follows.…”
Section: Navier Stokementioning
confidence: 99%
“…It should be noted that the Reynolds decomposition, which includes the breakdown of an instantaneous quantity into its time-averaged and fluctuating components, is the primary technique for deriving the RANS equations from the instantaneous Navier-Stokes equations. The separation of a variable (such as velocity u) into its mean (time-averaged) component (ū) and its fluctuating component (u′) is referred to as Reynolds decomposition [12]. The expressions for the continuity equation and the RANS equation are as follows.…”
Section: Navier Stokementioning
confidence: 99%
“…To calculate the bearing noise, the Proudman model is used [33]. In this way, the Proudman equation has been embedded into a numerical computation through CFD code [36]. For detail, to predict the bearing noise, the broadband noise source model in ANSYS is used [41].…”
Section: Governing Equationmentioning
confidence: 99%
“…In these studies mentioned earlier, the structure deformation (shaft and bearing) was neglected. It is crucial to evaluate the interaction effects of fluid and structure, as discussed by the recent literature, for example in [33][34][35][36]. It was revealed that the bearing deformation has a great effect on the tribological characteristics of lubricated journal bearing, and this effect cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Papadopoulos et al [25] established the CFD-THD lubrication model of textured pan-shaped pad thrust bearings and studied the influence of operating parameters and texture parameters on lubrication performance. Tauviqirrahman et al [26] solved the lubrication characteristics of bearings of different materials using a coupled CFD-FSI (Fluid-Structure Interaction) method and investigated the relationship between bearing materials and bearing friction noise. In order to obtain the nonlinear oil film force model of journal bearings based on CFD, it is necessary to extend the CFD lubrication analysis model of journal bearings to the transient flow field by using the dynamic mesh method.…”
Section: Introductionmentioning
confidence: 99%